The sources and magnitudes of Switzerland's gains from trade - Christian Hepenstrick (University of Zurich, Department of Economics, 2011)
This paper adapts the modern workhorse model of quantitative trade theory (Eaton and Kortum, 2002) as a measurement tool to quantify the magnitudes of Switzerland's gains from trade. I find that the importance of single trading partners for Switzerland's welfare is surprisingly small. The reason are reallocation effects - if trade between Switzerland and some partner country is inhibited, other supplier countries step into the breach so that the losses are limited. However, if one considers groups of countries, for example the EU, the welfare effects become large. In terms of policy this implies that whereas bilateral trade agreements may be important for particular industries per se, their relevance lies primarily in ensuring that the Swiss trade costs remain constant relative to trade costs within large trading blocks.
Keywords: F10; F11; F14; 330; gains from trade; Switzerland; development accounting; Außenhandelsgewinn; Handelsabkommen; Außenhandelselastizität; Schweiz